2021
DOI: 10.1002/jcsm.12816
|View full text |Cite
|
Sign up to set email alerts
|

Between‐study differences in grip strength: a comparison of Norwegian and Russian adults aged 40–69 years

Abstract: Background Identifying individuals with low grip strength is an initial step in many operational definitions of sarcopenia. As evidence indicates that contemporaneous Russian populations may have lower mean levels of grip strength than other populations in northern Europe, we aimed to: compare grip strength in Russian and Norwegian populations by age and sex; investigate whether height, body mass index, education, smoking status, alcohol use and health status explain observed differences and; examine implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
7
0
3
Order By: Relevance
“…It aligns with the findings from a study where the grip strengths of Tromsø7 participants and Russian Know Your Heart study participants aged 40–69 years were compared. The average Norwegian participant had a mean grip strength comparable to a 7-year younger Russian counterpart 57. This indicates that the nordic population might be comparatively healthier,58 thus limiting the generalisability of our findings to other populations across the globe.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It aligns with the findings from a study where the grip strengths of Tromsø7 participants and Russian Know Your Heart study participants aged 40–69 years were compared. The average Norwegian participant had a mean grip strength comparable to a 7-year younger Russian counterpart 57. This indicates that the nordic population might be comparatively healthier,58 thus limiting the generalisability of our findings to other populations across the globe.…”
Section: Discussionmentioning
confidence: 80%
“…The average Norwegian participant had a mean grip strength comparable to a 7-year younger Russian counterpart. 57 This indicates that the nordic population might be comparatively healthier, 58 thus limiting the generalisability of our findings to other populations across the globe. Only a subsample of our study population had information on both BMI and WC, and an even lower number had repeated measurements available for both exposures.…”
Section: Discussionmentioning
confidence: 89%
“…Sarcopenia, a progressive and generalized skeletal muscle disorder, leads to adverse outcomes such as falls, disability, cognitive decline, and mortality and a significant threat to the maintenance of independence [ 4 ], which can be estimated by a decrease in muscle mass and strength, and physical performance.…”
Section: Physical Performance Test For Sarcopeniamentioning
confidence: 99%
“…Several normative values for HGS have been established in people from Western countries 4,12–15 . However, there are variations in HGS values among countries, which could be attributed to significant differences in lifetime exposures, body size and composition 16 . The PURE study that assessed grip strength in adults aged 35–70 who reside in 21 countries suggested that individual HGS measurements should be interpreted using region‐specific reference ranges 17 .…”
Section: Introductionmentioning
confidence: 99%
“…4,[12][13][14][15] However, there are variations in HGS values among countries, which could be attributed to significant differences in lifetime exposures, body size and composition. 16 The PURE study that assessed grip strength in adults aged 35-70 who reside in 21 countries suggested that individual HGS measurements should be interpreted using region-specific reference ranges. 17 Although some studies have explored the HGS values among Asian people, 11,18,19 they focused on elders or in a selected population, for example, in healthcare industry workers, lacking data with a broad age range in a general unselected population.…”
Section: Introductionmentioning
confidence: 99%